Examining the effect of an aerobic exercise program on stress and triglycerides level in sedentary students: A pilot study - Singh, Sinku Kumar; Afroz, Nadeem (International Journal of Occupational Safety and Health, 2017)
Background: Stress is a risk factor for developing hypertension and cardiovascular diseases. The increased risk of cardiovascular diseases from chronic stress has been linked to increased plaque build-up as a result of elevated cholesterol, hardening of the arteries, change in the blood pressure, and abnormal working rhythm of the heart. The primary aim of this study was to examine the effects of Aerobic Exercise on stress and triglycerides. Methods: This study is a Pre-experimental Study - One Group Pre-test Post-test Design. A group of 17 sedentary male students whose age ranged between 19-28 years was enrolled in the study. The respondents were free of any type of smoking habit, consumptions of alcohol and drugs before the study. The study respondents participated in Aerobic Exercise Training program which was conducted for six weeks, four days a week and 45 minutes in a day. The pre-test and post-test were conducted before and after the intervention. Results: The mean age, height and weight of the Sedentary Students were 24.34 years, 172.31 cm and 69.22 kg respectively. Before an aerobic exercise program, 52.94% sedentary students reported mild stress, 29.41 % reported moderate stress and 17.64 % reported severe stress. Whereas, after aerobic exercise program, 58.82% sedentary students reported mild stress, 23.52 % reported moderate stress and only 11.64 % reported severe stress. The Pre-test mean score of Triglycerides was 147.649 mg/dl and the post test was 113.483 mg/dl. Conclusion: An aerobic exercise program may reduce stress and triglycerides levels in sedentary students. This research provides a platform for further research in this field with higher power and precision.